PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KEPEMILIKAN MANAJERIAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2021 - Sianturi, Sitra; Silalahi, Donalson (LPPM Universitas Katolik Santo Thomas Medan, 2023)
The purpose of this study was to determine and explain the effect of institutional ownership and managerial ownership on financial performance in LQ-45 companies listed on the Indonesian Stock Exchange for the 2018-2021 period, both simultaneously and partially. To achieve this goal, research was carried out on the Indonesia Stock Exchange using the purposive sampling method for 18 companies for the 2018-2021 period with 72 observations. The analysis technique used is a multiple linear regression model with descriptive statistical tests, classical assumption tests, and hypothesis testing. The results of this study indicate that institutional ownership has a significant and significant effect on financial performance, while managerial ownership has a positive and significant effect on financial performance. Simultaneously institutional ownership and managerial ownership have a positive and significant effect on financial performance with a value (R2) of 20%